Micro-catheter shaping electromagnetic heater - WANG WENLIANG; ZHANG QINGQIAO; GAO ZHIKANG; SHA JUNCHENG (2024)
The invention discloses a microcatheter shaping electromagnetic heater which comprises a shell, an electromagnetic heating coil, a timing key, a display screen, a single chip microcomputer, a heating circuit, a nixie tube driving circuit, a nixie tube and a power module. The upper surface of the shell is provided with a display screen and a timing button, the front end of the shell is provided with an electromagnetic heating coil, and the side surface of the shell is provided with a power interface; the single-chip microcomputer, the heating circuit, the nixie tube driving circuit, the nixie tube and the power module are all arranged in the shell, the single-chip microcomputer is connected with the heating circuit, the nixie tube driving circuit and the power module, the power module is connected with the heating circuit and the nixie tube driving circuit, and the nixie tube driving circuit is connected with the nixie tube. The heating element is the cylindrical electromagnetic heating coil which is hollow on